Monitoring International Labor Standards : Techniques and Sources of Information (National Academies Press, 2004)
"Increased attention to the role of labor standards in a more integrated global economy has led to a growing demand for information on compliance with core labor standards. Both traditional national and international agencies and a growing number of voluntary monitoring and reporting procedures in the private sector have acquired new vigor. The result has been a proliferation of sources of information." "This new book - which includes a comprehensive database structure - provides a framework within which to assess those data and compliance with core international labor standards. It represents progress toward having and interpreting all relevant information in one overall framework, including the integration of qualitative and quantitative information." "The book offers a first step toward the goal of providing an empirical foundation to monitor compliance with core labor standards. It provides a roadmap to existing data sources, their relevance to defined labor standards, their utility to decision makers in charge of assessing or monitoring compliance, and the cautions necessary to understand and use the information. It is resource for anyone working on international labor issues."--Jacket